Business in practice: integrating theory and reality in the analysis of Mudanca Motors business performance and leadership dynamics - Bannier, Hester Josje (2024)
This dissertation presents a comprehensive reflection on the business simulation performed as part of the Business in Practice Work Project, where the company managed in the simulation, Mudança Motors, navigated the complexities of the automotive industry. The dissertation is divided into two key parts. The first part offers a firm analysis of Mudança Motors' strategy, Sales & Marketing, and HR departments, using theoretical frameworks and industry comparisons to assess how the company navigated fleet electrification amid intense automotive competition. The second part offers a personal reflection on two critical incidents encountered during the team project. These incidents are examined through theoretical lenses, from which valuable leadership insights and skills are derived. Overall, this dissertation combines strategic business evaluation and personal development, offering a dual perspective on the challenges of managing a company as well as oneself in a dynamic team environment.